PENGARUH BIAYA SUMBER DAYA MANUSIA DAN PENGUKURAN NILAI SUMBER DAYA MANUSIA TERHADAP PELAPORAN AKUNTANSI SUMBER DAYA MANUSIA PADA PT BANK ACEH SYARIAH KANTOR PUSAT - Mulyati, Sri; Nafiza, Hayatun (Jurnal Akuntansi dan Keuangan, 2020)
This study aims to determine and analyze the effect of human resource costs and measurement of the value of human resources on the reporting of human resource accounting at PT Bank Aceh Syariah Head Office. This study uses primary data obtained by distributing questionnaires to all respondents. The samples in this study are selected using Purposive sampling. The sample in this study is 60 permanent employees at PT Bank Aceh Syariah. The data analysis method used is multiple linear regression with the help of SPSS 16.0. The results show that the cost of human resources affects the reporting of human resource accounting at PT Bank Aceh Syariah Head Office, and the measurement of the value of human resources affects the reporting of human resource accounting at PT Bank Aceh Syariah. Simultaneously, the cost of human resources and the measurement of the value of human resources affect the reporting of human resource accounting at PT Bank Aceh Syariah Head Office.Â